2015
DOI: 10.1002/j.0022-0337.2015.79.4.tb05895.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Surveys in Dental School Clinics: A Review and Comparison

Abstract: Health care is becoming more patient-centered and, as a result, patients' experiences of care and assessment of satisfaction are taken more seriously. Patient satisfaction inluences treatment cooperation, and better cooperation leads to healthier patients in the long term. This generalization clearly applies in the dental school clinic setting. Furthermore, dental school clinics' administrators and clinicians should know about the dimensions of their patient satisfaction in order to provide the highest quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 13 publications
1
39
0
6
Order By: Relevance
“…Students with various personality types may differ in their performance throughout their dental education. Ahmady et al found that dental students’ personality was related to patient satisfaction 12 . Smithers et al demonstrated that there was a need to differentiate between academic and clinical performance when investigating which factors predict success in dental school 4 .…”
Section: Four Temperament Groups In Keirsey Temperament Sorter II Witmentioning
confidence: 99%
“…Students with various personality types may differ in their performance throughout their dental education. Ahmady et al found that dental students’ personality was related to patient satisfaction 12 . Smithers et al demonstrated that there was a need to differentiate between academic and clinical performance when investigating which factors predict success in dental school 4 .…”
Section: Four Temperament Groups In Keirsey Temperament Sorter II Witmentioning
confidence: 99%
“…In particular, the intervention targets include organizational motivation, resources, staff attributes, climate, and teamwork. For instance, while the introduction of electronic health record (EHR) systems in dental schools has been a valuable tool for, among other areas, strategic planning 25 and promoting students’ critical thinking, 26 it may be important to hire and train patient service representatives or other staff who enter patient demographic and appointment information to focus on empathetic interactions with patients during these encounters 27 . In conversations with clinical colleagues at our own dental schools about the underlying reasons for the overwhelmingly positive experiences with dental school clinics, they suggested that the introduction of group practice leaders in the clinics has fostered a spirit of teamwork among our dental students and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…The intent is for dental educators to share effective practices and innovative ideas for the future, resulting in enhanced faculty development and satisfaction, improved student learning outcomes, and a more sustainable learning environment. Ultimately, these factors support the person‐centered care approach, resulting in greater patient satisfaction and improved oral health 6 …”
mentioning
confidence: 94%